Penguatan Peran Pemerintah Desa dalam Pembangunan Sosial Pemuda melalui Sepak Bola; Studi Kasus di Desa Towale, Kabupaten Donggala, Sulawesi Tengah - Gufran, Gufran; Samintang, Samintang; Pangeran, Ismail (Journal of Islamic Community and Development, 2025)
Sports play a strategic role in local social development, particularly in fostering youth potential. This study aims to analyze the role of the Towale Village Government in developing youth through football training and to identify the supporting and inhibiting factors of policy implementation. The study employed a descriptive qualitative approach, utilizing observation, in-depth interviews, and documentation. Eight key informants were purposively selected, including the village head, community leaders, and active youth participants in the village football program. The findings reveal that the village government acts as a strategic facilitator by providing sports facilities, encouraging public participation, and fostering collaboration between youth and the community. Supporting factors include budget allocation from village funds, active involvement of community figures, and participatory communication. However, financial limitations and high operational costs of tournaments remain major obstacles to program sustainability. These findings emphasize the importance of synergy between village authorities and local communities in building an inclusive, sustainable, and impactful community-based sports ecosystem for youth character development.